Modeling and evaluation of the effectiveness of the operation of Danube rice irrigation systems taking into account environmental requirements - Turchenyuk, Vasyl; Kozishkurt, Svitlana; Prykhodko, Natalia; Voitsekhovych, Nazarii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Abstract — A mathematical modeling approach was employed to establish a suite of indicators for assessing the efficiency of Danube rice irrigation systems. The proposed indicators facilitate the identification of rational management strategies, including methods, regimes, and schemes for regulating the natural and reclamation processes of irrigated lands. This takes into account the unique characteristics of rice systems while ensuring compliance with current environmental regulations and principles of sustainable development. Анотація – За результатами математичного моделювання обґрунтовано сукупність показників як критеріїв для оцінки ефективності функціонування Придунайських рисових зрошувальних систем. Обґрунтований перелік показників дає можливість визначити раціональні способи, режими та схем регулювання природно-меліоративного режиму на зрошуваних землях, з урахуванням специфіки рисових систем, що відповідають сучасним екологічним вимогам і забезпечують сталий розвиток таких систем.